Characterization factors for ocean acidification impacts on marine biodiversity. (7th April 2022) - Scherer, Laura; Gürdal, İrem; van Bodegom, Peter M.
Abstract: Rising greenhouse gas emissions do not only accelerate climate change but also make the ocean more acidic. This applies above all to carbon dioxide (CO2 ). Lower ocean pH levels threaten marine ecosystems and especially strongly calcifying species. Impacts on marine ecosystem quality are currently underrepresented in life cycle assessments (LCAs). Here, we developed characterization factors for the life cycle impact assessment of ocean acidification. Our main contribution was developing new species sensitivity distributions (SSDs), from which we derived effect factors for different impact perspectives: Marginal, linear, and average changes for both the past and four future emission scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5). Based on a dataset that covered five taxa (corals, crustaceans, echinoderms, fishes, molluscs) and three climate zones, we showed significantly higher sensitivities for strongly calcifying than slightly calcifying taxa and in polar regions compared to tropical and temperate regions. Experimental duration, leading to acute, subchronic, or chronic toxicological endpoints, did not significantly affect the species sensitivities. With ocean acidification impacts still accelerating, the future‐oriented average effects are higher than the marginal or past‐oriented average effects. While our characterization factors are ready for use in LCA, we also point to opportunities for improvement in future developments.